2007
DOI: 10.1080/17450390701431953
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial protein meal produced on natural gas replacing soybean meal or fish meal in broiler chicken diets

Abstract: The effects of replacing soybean meal or fish meal with 2, 4 or 6% bacterial protein meal (BPM) on growth performance, ileal digestibility of amino acids and sensory quality of meat, were examined using 630 broiler chickens. Weight gain from 7-32 days of age did not differ significantly among the treatments. Efficiency of feed conversion was increased when BPM replaced soybean meal, and abdominal fat deposition tended to decline. Feed conversion was not affected when BPM replaced fish meal. Amino acid digestib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…Previous studies have shown that feeding BPM to broiler chickens results in similar or improved growth up to 60 g/ kg (Skrede et al, 2003;Schøyen et al, 2007b), but reduced growth rates at higher inclusion concentrations of 80 and 100 g/kg, when replacing SBM (Skrede et al, 2003). Significantly better FCE has also been obtained with increasing concentrations of up to 100 g/kg BPM (Skrede et al, 2003;Schøyen et al, 2007a). In contrast, we found that adding BPA to diets resulted in reduced BWG and FI, and decreased FCE, especially at high concentrations of 80 and 120 g/kg.…”
Section: Discussioncontrasting
confidence: 42%
See 4 more Smart Citations
“…Previous studies have shown that feeding BPM to broiler chickens results in similar or improved growth up to 60 g/ kg (Skrede et al, 2003;Schøyen et al, 2007b), but reduced growth rates at higher inclusion concentrations of 80 and 100 g/kg, when replacing SBM (Skrede et al, 2003). Significantly better FCE has also been obtained with increasing concentrations of up to 100 g/kg BPM (Skrede et al, 2003;Schøyen et al, 2007a). In contrast, we found that adding BPA to diets resulted in reduced BWG and FI, and decreased FCE, especially at high concentrations of 80 and 120 g/kg.…”
Section: Discussioncontrasting
confidence: 42%
“…The decreased litter quality at d 32 in the birds fed BPA, despite a lower FI in this period, might be related to the increased digesta viscosity of these birds; this is in agreement with data reported by Leeson and Summers (2001). Schøyen et al (2007a) also reported stickier droppings and poorer litter quality in chickens fed BPA, but not with BPM. The increase in jejunal viscosity when feeding BPA compared with BPM may be a result of increased exposure of the cell membrane and cell wall components, resulting in increased interaction with constituents in the intestinal lumen.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations